In vitro Antioxidant and Free Radical Scavenging Activity of the Bark of Dillenia indica L. (Bangladesh Pharmaceutical Journal, 2022)
The aim of the study was to explore the antioxidant and free radical scavenging activity of bark of Dillenia indica L. The methanolic extract (CME) of coarse powder of the dried bark was fractionated with pet-ether (PETF), chloroform (CHF), and water (AQF) and each fraction was investigated for antioxidant and free radical potentials. The phenolic contents of CME, CHF, PETF and AQF were found to be 90.2, 171.1, 52.1 and 158.1 and flavonoid contents 182.6, 340.2, 285.9, and 362.6 mg of GAE/g of dried extract, respectively. The total antioxidant activity of CME, PETF, CHF, AQF and standard catechin in terms of absorbance were 0.373, 0.707, 0.88, 1.051 and 0.804, respectively at 160 μg/ml concentration indicating AQF possessing the highest total antioxidant activity. In DPPH radical scavenging activity, the AQF and CHF showed potential radical scavenging activity followed by CME and PETF with IC50 values of 1.5, 2.5, 23 and 61 μg/ml, respectively, whereas standard ascorbic acid showed IC50 at 8 μg/ml. Among the extractives, AQF and CHF exhibited potent hydroxyl radical scavenging activity with IC50 values of 49.0 and 42 μg/ml followed by CME and PETF with IC50 of 86 and 168 μg/ml, respectively. In ferric-reducing antioxidant assay, AQF, CHF and CME (absorbance 2.262, 2.418 and 2.157, respectively) showed higher activity than that of standard (1.793) followed by PETF (absorbance 0.593). Since polyphenols like flavonoids play a vital role in controlling antioxidants, polyphenol rich extracts are potent source of antioxidants. Our data showed that the chloroform fraction of the bark of D. indica provided highest polyphenols and antioxidant activities, hence, can be used further as a source of natural antioxidants.Bangladesh Pharmaceutical Journal 25(1): 38-43, 2022 (January)